SAFETY OF PEDIATRIC COMBINATED VACCINE FOR DIPHTHERIA, PERTUSSIS, TETANUS, POLIO AND HAEMOPHILUS INFLUENZA TYPE B IN THE PRIMARY IMMUNIZATION AND FIRST BOOSTERISATION - N. D. Chernova; I. A. Ivanova; G. M. Demchuk; Y. E. Cousina; O. B. Valetova (Union of pediatricians of Russia, 2012)
The results of studies of the safety of a combined five-component pediatric vaccine to prevent diphtheria, pertussis, tetanus, polio, Haemophilus influenzae type b (DTaP-IPV//Hib) in children in the primary vaccination and for the first boosterisation are shown. On the introduction of 208 doses of 264 (75.8%) there were no any local or general reactions registered. The registered local or general reactions occurred usually on the 1st day after vaccination and lasted for 1-2 days. Local reactions with a diameter ≥ 2 cm were reported in 2 cases (0.8%) and did not exceed the diameter of 2 cm. Increased body temperature ≥ 38,5°C was recorded in 3 cases (1.1%) and was not higher than 39,0°C. There have been fixed no cases of anaphylactic reactions, seizures, encephalitic reactions. Due to the high-profile security vaccine DTaP-IPV//Hib is suitable for wide application in outpatient conditions for the standard routine and catch-up vaccination of healthy children and children with underlying medical conditions.